QUALITY CONTROL OF FLOUR AND BAKERY PRODUCTS BY SCORE - Odil Rustamov; Ra’no Akramova (Journals Park Publishing, 2022)
The article provides a manual of standard generally accepted and methods for the study of bakery products with a logical structure that allows you to easily orient all the necessary methods for the study of bakery products.
Keywords: bakery products; GOST; organoleptic parameters